The preposition avec in a contemporary literary corpus - Dedkova, Iva (Romanica Olomucensia, 2016)
The paper deals with the use of the preposition avec (with) in a corpus of a literary text from contemporary French. It analyses its occurrences, main morphosyntactic features and different values. The results of linguistic research conducted in France complete the issue under consideration.
Keywords: preposition avec (with); literary text; occurrences; values; comitative.